Reinterpretation of Malvinoconularia cahuanotensis (Braniša and Vaněk) from the Devonian Altiplano and Western Andean Cordillera, Bolivia, South America - Leme, Juliana de Moraes [UNESP]; Simões, Marcello Guimarães [UNESP]; Van Iten, Heyo (My University, 2006)
The holotype of Malvinoconularia cahuanotensis (Braniša and Vaněk) (Devonian, Bolivia), the type species of the monospecific genus Malvinoconularia Babcock et al., is redescribed and refigured. M. cahuanotensis exhibits several gross morphological features that together are uniquely shared with Reticulaconularia baini (Babcock and Feldmann). In both taxa, the transverse ribs are nodose, the inter-spaces bear longitudinal ridges (bars or crests) that are collinear (line up) across the transverse ribs, and the longitudinal centerline (midline) of the faces is marked by a subdued ridge. Additionally, the two species may also be similar in the anatomy and external ornament of the corner sulcus. The slightly undulose geometry of the transverse ribs of M. cahuanotensis also is exhibited by certain specimens of Reticulaconularia; however, whether this feature is primary or taphonomic in origin is unclear at present. Together, these similarities suggest that the genus Malvinoconularia probably is a junior synonym of the genus Reticulaconularia. © Asociación Paleontológica Argentina.
Keywords: Bolivia; Cnidaria; Conulariids; Devonian; Systematics; invertebrate; morphology; paleoecology; taphonomy; taxonomy; Altiplano; South America